Occupational Stress and How to Confront It: A Case Study of a Hospital in Shiraz - Tahereh Shafaghat; Mohammad Kazem Rahimi Zarchi; Zahra Kavosi (Baqiyatallah University of Medical Sciences, 2018)
Background: Although all jobs can be stressful, occupational stress is an important issue in jobs that deal with human health. Evidence indicates that nursing is a stressful occupation. Objective: This research evaluated factors affecting occupational stress and strategies for coping with it. Methods: This cross-sectional descriptive-analytic study was conducted in 2015. The study population comprised all nurses at Shahid Rajaee hospital, from whom 190 nurses were selected by random sampling. Data was collected by questionnaire and analyzed using SPSS software (version 19), Pearson correlation coefficient tests, Mann-Whitney tests, and t tests. Results: Occupational stress was rated as moderate among the studied nurses. Significant positive correlations were found between occupational stress level and less effective coping method, occupational stress level and work experience level, and ineffective coping methods and age. Moreover, a significant difference was seen between men and women in terms of emotion-focused coping. Conclusion: According to the research findings, occupational stress was at a moderate level among the studied hospital nurses, indicating that the authorities need to focus on efforts to reduce occupational stress for nurses.